Legal Protection of Academic Paper Written by Students and Lecturers - Gaidar Kenny Marcapada (FH 16 UMY 110, 2016)
Cribbing of scientific work may decrease creativity creator to work, which is indispensable to the intelligence of the nation and acceleration to development of the country. Has made regulation no 28 of 2014 on intellectual property right is very appropriate. Plagiarism is generally understood as making the writing containing ideas of others are recognized as his own creation. Related with the creation process, the law requires that a book or paper like it should be authentic and original. Legal protection against scientific paper is still weak in the application in Indonesia. Scientific paper is a very important thing to be guarded of authenticity. The research use the Normative Legal Research by qualitative method. The research found the scientific paper understanding is low and the law enforcement of the Academic Paper Research is worst. Keyword: Copyright, Legal Protection for scientific paper, Plagiarism